Ecologization and Its Socioeconomic Implications: Exploring the Influence of Environmental Values on Students' Attitudes Toward Green Entrepreneurship - Kouteiba Selmane; Chafik Chatter; Samir Salmi (SocioEconomic Challenges)
Environmental issues pose a serious global and local challenge, leading to significant social and economic risks. Therefore, these challenges require urgent action and a shift in values and behaviours, especially among young people, who are the driving forces for sustainable development and green entrepreneurship. This study explores the effect of environmental values on attitudes toward green entrepreneurship. Specifically, it focuses on three types of environmental values: intrinsic values, relational values, and instrumental values. The study was conducted on 275 final-year (third-year) undergraduate students from the University of Jijel, Algeria, during the second semester of 2024. A questionnaire was used to collect data. The questionnaire consists of 22 statements: (7 items) intrinsic values, (6 items) relational values, (4 items) instrumental values, and (5 items) the attitude towards green entrepreneurship. The points of view of the sample were assessed on a five-point Likert scale. SPSS version 23 was utilized for data entry and statistical analysis, employing various statistical techniques to process the study’s results, including Pearson's correlation, Cronbach's alpha, skewness and kurtosis coefficients, means and standard deviations, Variance Inflation Factor (VIF), tolerance values, and standard multiple regression analysis. The study concluded that the surveyed students exhibited a very high level of environmental values, with a mean score of 4.28. Instrumental values ranked highest, with a mean score of 4.51, followed by intrinsic values, with a mean score of 4.24, and finally, relational values, with a mean score of 4.09. Students’ attitudes toward green entrepreneurship were positive, with a mean score of 3.78. The study also found that environmental values significantly influence students' attitudes toward green entrepreneurship, with this impact being attributed to relational values. Given the rising environmental concerns worldwide, there is a growing necessity to embrace environmental values and green entrepreneurship as solutions to these challenges. The findings and recommendations of this study have important practical implications, as they are expected to draw the attention of decision-makers to the need to develop environmental values and attitudes towards green entrepreneurship among youths.